The impact of the Omani values program on the moral intelligence of early education children in Sultanate of Oman - Al-Mushaiqri, Mahfouda Rashid Said (Journal of Educational and Psychological Sciences, 2023)
The current research aimed at measuring the impact of the Omani values program on the moral intelligence of children in the Sultanate of Oman. The researcher also adopted the semi-experimental approach, and the current research presented the Omani Values Program for children aged (4-6) years in the Sultanate of Oman. The sample consisted of (30) children in the experimental group and (30) children in the control group. The researcher used a scale of two pictures to measure the children's behaviour before and after the experiment. The program for the study also included (16) training sessions that were provided during (8) weeks, at a rate of one hour for each session.The results of the study were in favor of the experimental group that was exposed to the Omani values programme. It was noted that their moral intelligence improved after joining the Omani Values Programme, compared to the control group that did not undergo the program, as well as the development of the moral intelligence of the children of the experimental group themselves compared to their behavior before joining the program. The results also showed that there were no statistically significant differences between males and females in the Omani values program in moral intelligence on the two axes of empathy and tolerance. It showed that there are differences between males and females in respect axis in favor of males. The study presented a set of recommendations, the most important one was: Training students at all academic levels on Omani values.
Keywords: Omani values; moral intelligence; early education